Microbial quality of mixed salad greens and selected fresh and dried herbs - Woo, Daniel Lee, author; Bunning, Marisa, advisor; Goodridge, Larry, committee member; Stone, Martha, committee member (Colorado State University. Libraries, 2010)
Direct marketing has been growing in the Western U.S., with 2007 sales of direct-marketed agricultural products totaling nearly $142.6 million in Colorado, New Mexico, Oregon, Idaho, Nevada and Washington-more than twice the 1997 sales level for the region. In addition, the number of farms engaging in direct sales to consumers grew by more than 20% to 18,274 in 2007. With increasing foodborne outbreaks linked to produce consumption, more research is needed to fill in the gaps of knowledge on the microbiological quality of leafy salad greens. Limited research has been conducted on the microbial safety and quality of farmers' market leafy salad greens. This study surveyed the microbial quality of salad greens from Larimer County farmers' markets in conjunction with salad mixes from a local supermarket. Leafy salad greens were obtained weekly for a period of four weeks from September to October, 2009, from both farmers' markets and supermarkets. Total aerobic and coliform counts were assessed within 48 hours of obtaining the samples via plating onto Petrifilm plates, then following one week of storage at refrigeration temperatures to observe changes in the microbial load. In addition, handling methods and temperatures were also recorded. Gloves and tongs were not used by vendors when handling salad greens. The vendors surveyed also lacked adequate refrigeration or ice for holding salad greens. Farmers' market salad greens were lower than supermarket salad greens in terms of initial aerobic plate counts. Both farmers' market and supermarket salad greens had no detectable levels of Escherichia coli and low levels of coliforms. After 1 week of storage, aerobic counts were higher in all samples (P<0.05). Coliform counts tended to decrease in all samples but no significant differences were observed (P>0.05). The results reiterate the need for consumers to thoroughly wash their salad greens. Further research should be conducted to assess the microbial quality o~ other produce at local farmers' markets. Herbs are often used in cooking to add aroma and flavor to foods. Consumers may choose to dry herbs from their garden or purchased from the market. Herbs, like other agricultural produce, may be exposed to a wide range of potential microbial contamination. There is currently little research on safe drying practices of herbs at home. Microwaving herbs is a potentially popular and time-saving approach for drying herbs at home. This research project investigated the impact of three drying methods (microwave, dehydrator, and conventional air drying) for improving the microbial quality of dried parsley and cilantro. Herb samples were obtained weekly from a local supermarket for a 2 month period from January to March, 2010. Standard guidelines from Oregon State University Extension service were followed for microwave drying of herbs. The manufacturer's drying temperatures/times were used for drying herbs in a dehydrator. Herbs were also air-dried for 1 week. Microbial testing was performed using plating onto 3M Petrifilm and when counts were below the detection limit, via the Most Probable Number (MPN) method. Microwave drying provided the greatest reduction in aerobic counts of bacteria in herbs. All drying methods reduced coliform counts to undetectable amounts; however, the determination of the effectiveness of each drying method in comparison with others for reducing the coliform count was complicated by the low initial load of coliforms in herbs used in the study.
Keywords: Salad greens; Herbs; Farmers' markets; Food contamination -- Risk assessment